PRINSIP KERJA SAMA DALAM TRANSAKSI JUAL BELI ANTARA PAMAN SAYUR DAN PELANGGAN: TINJAUAN PRAGMATIK - jahdiah diah (Kelasa, 2021)
The objective of this research is to describe the violation and the use of the cooperative principle that is classified based on four maxims; they are maxim of quantity, the maxim of quality, the maxim of relation, and the maxim of manner.  This research uses the basic theory of pragmatic by focusing on the cooperative principle stated by Grice. This research uses a descriptive method. The data source of this research is the speech of the vegetable seller and his customers.  Data collection was taken from January--Febuary 2020. The data analysis is using a contextual heuristic method. Based on the result of the study, there are two violations of the maxim of quantity, two data of violations of the maxim of relation. The use of the cooperative principle is more commonly found in this research, namely, there are ten cooperative principles, three maxims of quantity, one maxim of quality, four maxims of relation, and two maxims of manner.